Vitellogenins - Yolk Gene Function and Regulation in Caenorhabditis elegans - Perez, Marcos Francisco; Lehner, Ben (Frontiers in Physiology, 2019)
Vitellogenins are a family of yolk proteins that are by far the most abundant among oviparous animals. In the model nematode Caenorhabditis elegans, the 6 vitellogenins are among the most highly expressed genes in the adult hermaphrodite intestine, which produces copious yolk to provision their eggs. In this article we review what is known about the vitellogenin genes and proteins in C. elegans, in comparison with vitellogenins in other taxa. We argue that the primary purpose of abundant vitellogenesis in C. elegans is to support post-embryonic development and fertility, rather than embryogenesis, especially in harsh environments. Increasing vitellogenin provisioning underlies several post-embryonic phenotypic alterations associated with advancing maternal age, demonstrating that vitellogenins can act as an intergenerational signal mediating the influence of parental physiology on progeny. We also review what is known about vitellogenin regulation – how tissue-, sex- and stage-specificity of expression is achieved, how vitellogenins are regulated by major signalling pathways, how vitellogenin expression is affected by extra-intestinal tissues and how environmental experience affects vitellogenesis. Lastly, we speculate whether C. elegans vitellogenins may play other roles in worm physiology.